(untitled) (Research, Society and Development, 2022)
The objective of this work was to carry out a literature review on the use of fluoride for the prevention and treatment of caries. For this, a search was carried out in the PubMed scientific database using the following keywords: dental caries, fluoride (fluoride), prevention, treatment and toxicity. Inclusion criteria included: (1) clinical studies or literature reviews; (2) published between 2000 and 2022; (3) in Portuguese or English; (4) with full text available. Exclusion criteria were: articles published outside the selected time period, methodology, or languages, as well as articles with the full text unavailable. In all, 31 articles were selected to compose this research. According to the results, the use of fluoride in the prevention of caries is based on the ability of this element to restore the balance of the demineralization and remineralization process of dental enamel. It is a versatile alternative, present in public health policies and that can be accessed in different ways, both at home and in the office. It was concluded that the use of fluoride is an important alternative for the prevention of dental caries, being considered a safe method that produces significant results in reducing the prevalence of this pathology.